Estudio sobre el desarrollo de las relaciones entre China y América Latina (SinoLATAM) en el contexto de la globalización. (2016)
With the steady growth of economic globalization and global governance of international affairs, the relationship between China and Latin America has demonstrated a stable and rapid development trend. In the new era, China and Latin America should strengthen their ties in the theme of “peace and development”, establish a community of common destiny and build a cooperative community win-win community for common development, so as to form an invincible community of common culture. Though the relations between China and Latin America (SinoLATAM) face a series of internal and external contradictions, it is necessary to see the wide perspectives that are behind the above mentioned contradictions in order to promote the steady development of bilateral and multilateral relations, deepen political trust, expand areas of economic and commercial cooperation, increase the reciprocity of win-win and lay a solid foundation for the global development of China and Latin America.